A positive diagnostic strategy is safe and saves endoscopies in patients with irritable bowel syndrome: A five‐year follow‐up of a randomized controlled trial. Issue 3 (7th October 2020) - Engsbro, Anne Line; Begtrup, Luise M.; Haastrup, Peter; Storsveen, Maria Munch; Bytzer, Peter; Kjeldsen, Jens; Schaffalitzky De Muckadell, Ove; Jarbøl, Dorte Ejg
Abstract: Background: Previously, the diagnosis of irritable bowel syndrome (IBS) required exclusion of organic causes by extensive diagnostic testing. Newer guidelines recommend IBS as a positive diagnosis based on symptoms with limited testing. We investigated the long‐term safety and impact on use of health resources of a positive diagnostic strategy compared to a strategy of exclusion in patients with symptoms compatible with IBS. Methods: In 2008‐2010, primary care patients aged 18‐50 years fulfilling the Rome III criteria for IBS without alarm signals were randomized to a positive diagnostic strategy (limited blood tests, n = 150) or a strategy of exclusion (extensive blood tests, fecal samples for intestinal parasites, and sigmoidoscopy with biopsies, n = 152). At five years, hospital‐registered diagnoses and use of health resources including lower endoscopies were retrieved from national registries. Participants provided 5‐year data on Rome III criteria for IBS, severity of symptoms, and quality of life. Key results: Baseline mean age was 31.4 (SD 9.1) years; 79% were female. No cases of celiac disease, and gastrointestinal or gynecological cancers were diagnosed within five years. Negligible and comparable numbers were diagnosed with inflammatory bowel disease, benign gynecological conditions, and upper GI conditions in the two groups. The positive diagnosis strategy carried a higher number of lower endoscopies from year 1 to 5 (23 patients versus 13 patients in the exclusion group), but overall saved endoscopies. Conclusions & Inferences: A positive diagnosis of IBS was as safe as a diagnosis of exclusion in a five‐year perspective and saved lower endoscopies; the study was registered at ClinicalTrials.gov numbers: NCT00659763/NCT01153295. Abstract : Compared to a diagnosis of exclusion, a positive strategy uses fewer lower endoscopies, has similar organic findings and similar quality of life after five years in patients with symptoms compatible with IBS. This supports current recommendations of a positive diagnosis in IBS.